2000
DOI: 10.1161/01.hyp.36.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Reduced Nitric Oxide/cGMP–Mediated Vasorelaxation in Transgenic Mice Overexpressing Endothelial Nitric Oxide Synthase

Abstract: Abstract-NO, constitutively produced by endothelial NO synthase (eNOS), plays a key regulatory role in vascular wall homeostasis. We generated transgenic (Tg) mice overexpressing eNOS in the endothelium and reported the presence of reduced NO-elicited relaxation. The purpose of this study was to clarify mechanisms of the reduced response to NO-mediated vasodilators in eNOS-Tg mice. Thoracic aortas of Tg and control mice were surgically isolated for vasomotor studies. Relaxations to acetylcholine and sodium nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
75
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 28 publications
11
75
0
Order By: Relevance
“…We established mice overexpressing eNOS in the vascular endothelium exhibited a NO/cGMPdependent decrease in blood pressure, 2 whereas we also found that eNOS overexpression reduced the sGC activity and PKG expression leading to reduction of endotheliumdependent or endothelium-independent activities. 12 This raised the possibility that continuous activation of endogenous NO may impair angiogenesis. Our present study thus extended the work of Murohara et al 11 to establish that endogenous NO production enhances angiogenesis in hindlimb ischemia affecting neither ischemia-induced VEGF expression nor VEGF-mediated Akt-eNOS signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We established mice overexpressing eNOS in the vascular endothelium exhibited a NO/cGMPdependent decrease in blood pressure, 2 whereas we also found that eNOS overexpression reduced the sGC activity and PKG expression leading to reduction of endotheliumdependent or endothelium-independent activities. 12 This raised the possibility that continuous activation of endogenous NO may impair angiogenesis. Our present study thus extended the work of Murohara et al 11 to establish that endogenous NO production enhances angiogenesis in hindlimb ischemia affecting neither ischemia-induced VEGF expression nor VEGF-mediated Akt-eNOS signaling.…”
Section: Discussionmentioning
confidence: 99%
“…2,12 The tissues remaining after cGMP measurement were digested by use of a bicinchoninic acid protein assay kit (Pierce). Plasma nitrite and nitrate (NOx) were measured by the Griess method, as previously described.…”
Section: Cgmp Assay and Measurement Of Noxmentioning
confidence: 99%
See 1 more Smart Citation
“…10 We also found that the basal eNOS activity in the vessels showed a 7-fold increase and that acetylcholineinduced NO production was elevated 3-fold in eNOS-Tg mice compared wild-type mice. 10,11 In the present study, to clarify the effects of chronic NO overproduction on vascular remodeling, particularly on lesion formation, we examined, with the use of eNOS-Tg mice, the mouse carotid artery vascular remodeling model 12 in which the endothelium remains uninjured.…”
mentioning
confidence: 99%
“…It is likely that the fall in plasma NOx following statin treatment alone is the result of negative feedback due to excess NO bioavailability and thereby having no adverse effects on the brain. Chronic increases in NO have been reported to down-regulate sGC expression (33) and to increase phosphodiesterase function (34), lowering the bioavailability of NO. This idea is consistent with dexamethasone-induced reductions in the concentration of the vasodilator gas with deleterious effects on the brain, vs. effects of statins in dexamethasone-treated pups replenishing appropriate NO concentrations and therefore, protecting the brain.…”
Section: Articlesmentioning
confidence: 99%